Efektivitas Cognitive Behavioural Therapy (CBT) terhadap Fatigue Pasien Hemodialisis - Wakanno, Grace Jeny; alahatu, Olivia T; Irawati, Diana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to evaluate the application of Cognitive Behavioral Therapy (CBT) in hemodialysis patients who experience fatigue based on the results of the latest research (Evidence Based Nursing Practice) at RSUD Dr. M. Haulussy Ambon. The method used is quasi-experimental with a pretest and posttest design approach with control group. The research results based on the homogeneity test of respondent characteristics found that there were no significant differences (p>0.05) in the intervention group and the control group. There was a significant improvement in fatigue in the intervention group (p=0.000). In conclusion, there is an influence of Cognitive Behavioral Therapy (CBT) on fatigue in patients undergoing hemodialysis. Key words: Behavioral, Cognitive, Fatigue, Hemodialysis, Therapy